Late therapeutic intervention with a respiratory syncytial virus L‐protein polymerase inhibitor, PC786, on respiratory syncytial virus infection in human airway epithelium. (2nd May 2018) - Brookes, Daniel W; Coates, Matthew; Allen, Heather; Daly, Leah; Constant, Samuel; Huang, Song; Hows, Mark; Davis, Amanda; Cass, Lindsey; Ayrton, John; Knowles, Ian; Strong, Pete; et al.
Abstract : Background and Purpose: Effective anti‐respiratory syncytial virus (RSV) agents are still not available for clinical use. Current major targets are virus surface proteins, such as a fusion protein involved in viral entry, but agents effective after RSV infection is established are required. Here we have investigated the effects of late therapeutic intervention with a novel inhaled RSV polymerase inhibitor, PC786, on RSV infection in human airway epithelium. Experimental Approach: Air liquid interface‐cultured bronchial or small airway epithelium was infected with RSVA2. PC786 was applied apically or basolaterally once daily following peak virus load on Day 3 post inoculation. Apical wash was collected daily for determination of viral burden by PCR and plaque assay (primary endpoints) and biomarker analyses. The effects were compared with those of ALS‐8112, an anti‐RSV nucleoside analogue, and GS‐5806, a fusion‐protein inhibitor, which were treated basolaterally. Key Results: Late intervention with GS‐5806 did not show significant anti‐viral effects, but PC786 produced potent, concentration‐dependent inhibition of viral replication with viral load falling below detectable limits 3 days after treatment commenced in airway epithelium. These effects were superior to those of ALS‐8112. PC786 showed inhibitory activities against RSV‐induced increases of CCL5, IL‐6, double‐strand DNA and mucin. The effects of PC786 were also confirmed in small airway epithelium. Conclusion and Implications: Late therapeutic intervention with the RSV polymerase inhibitor, PC786, reduced the viral burden quickly in human airway epithelium. Thus, PC786 demonstrates the potential to be an effective therapeutic agent to treat active RSV infection.